DEVELOPMENT OF WALKING TRACK DEVICE FOR FUNCTIONAL RECOVERY ANALYSIS AFTER EXPERIMENTAL SCIATIC NERVE INJURY - Tsymbaliuk, V.I.; Petriv, T.I.; Molotkovets, V.Y.; Vasyliev, R.G.; Tatarchuk, M.M.; Burkush, I.I. (World of Medicine and Biology, 2017)
The article is devoted to developing devise for Walking track test in rats after experimental sciatic nerve injury. Gradual gait improvement reflects the nerve function recovery in the temporal aspect. Its essence lies in getting rat footprints on paper, witch are analyzed. Then functional sciatic nerve index (SFI) is calculated using a special formula in experimental and intact limbs of the rats. The experiment was performed on outbred male rats (n=15) whom autoneuroplasty was performed. Animals were grouped as following: 1(4) (n=7) tested after 4 weeks of experiment and 1(8) (n=8) – after 8 weeks of experiment. The results shows that functional sciatic nerve regeneration continues during 4 till 8 weeks. This process reflected in SFI improving. Developed walking track device allows to obtain rat footprints simply and fast. The use of Walking track test by using developed device provides a non-invasive method of assessing the functional status of the sciatic nerve during the regeneration process.
Keywords: Walking track; sciatic functional index; sciatic nerve injury; functional recovery